The laurent series for the quaternionic case - Borges Neto, Manoel Ferreira [UNESP]; Marão, José Antonio Pires (Academic Publications, 2014)
The present work has the scope to show the Laurent Series for quaternionic functions. It will be shown that the Laurent Series for the Quaternionic Case is analogous to the textbook case of Complex Analysis [1]-[2] already well established.
Keywords: Laurent series; hypercomplex functions; quaternionic functions